ChemInform Abstract: Palladium‐Catalyzed ortho‐Halogenation of Diaryl Oxime Ethers. Issue 3 (January 2015) - Bhattarai, Bijay T.; Adhikari, Sarju; Kimball, Elizabeth A.; Moore, Jane N.; Shaughnessy, Kevin H.; Snowden, Timothy S.; Fronczek, Frank R.; Dolliver, Debra D.
Abstract The Pd‐catalyzed halogenation of diaryl ketoxime ethers provides predominantly the corresponding ortho monohalogenated products (II) and (IV).